RNA-binding proteins and translational regulation in axons and growth cones - Hornberg, Hanna K.; Holt, Christine (Frontiers in Neuroscience, 2013)
RNA localization and regulation play an important role in the developing and adult nervous system. In navigating axons, extrinsic cues can elicit rapid local protein synthesis that mediate directional or morphological responses. The mRNA repertoire in axons is large and dynamically changing, yet studies suggest that only a subset of these mRNAs are translated after cue stimulation, suggesting the need for a high level of translational regulation. Here, we review the role of RNA-binding proteins as local regulators of translation in developing axons. We focus on their role in growth, guidance and synapse formation, and discuss the mechanisms by which they regulate translation in axons.